The Royal Descent and the Past Glory of the Demak Sultanate as the Builders of Coastal Javanese Resistance in the Novel Penangsang (Tembang Rindu Dendam) - Waluyo Sukarjo (EDP Sciences, 2021)
Arya Penangsang was a Duke of Jipang who ruled in the mid-16th century. He is the grandson of Sultan Patah, the founder of the Sultanate of Demak. The Babad Tanah Djawi tells the story of Arya Penangsang killing Pangeran Mukmin to take back his father's rights. Pajang's attack succeeded in killing Arya Penangsang. The bad image of Arya Penangsang was built by the Sultanate of Pajang. Meanwhile, the Mataram Sultanate, Surakarta Palace, and Yogyakarta Palace continued for hegemony. Meanwhile, for the coastal community of Java, Arya Penangsang is a respected figure. The object of research is the novel Penangsang (Tembang Rindu Dendam) which was published in 2010. The purpose of this study is to explain the problem of resistance, namely disobedience in the context of the relationship between power and domination [1]. This study uses library and ethnographic methods by utilizing this new historicism (NH) approach which links literary texts with non-literature. The results of this study indicate three important messages. First, people interpret their social environment in terms of their past history. Second, Arya Penangsang is a prince who became a local hero. Third, past history is a builder of cultural ties.